Diseño e implementación de un banco de pruebas para un generador de corriente continua, aplicando cargas variables para la visualización de parámetros técnicos de funcionamiento a través de software labview, para el laboratorio de máquinas eléctricas en la Universidad Técnica de Cotopaxi Latacunga 2015 - 2016 - Monga Sánchez, Ángel Ramiro (2016)
The present investigation has as purpose to design and implement a test bank on a continuous current generator, applying variable loads for the technical parameters operation's visualization through the LabView software, for the Electric Machines Lab at Cotopaxi Technical University. As well as the use correct of the methods of mensuration of technical parameters that one can obtain. The scientific content is based on a solid theoretical foundation, about the function and operation of continues current’s the generators. It also contains technical of investigation that were used in this project, the same as it is described the instruments that will help for the compilation and tabulation of information for the investigation development. In the progress of the proposal it will detail the main parameters of the elements, instruments and teams which it was used for the elaboration of the Test Bank, as well as their analysis of the tests….